Numerical Solution of the Two-Phase Obstacle Problem by Finite Difference Method - Arakelyan, Avetik; Barkhudaryan, Rafayel; Poghosyan, Michael (Armenian Journal of Mathematics, 2015)
We propose an algorithm to solve the two-phase obstacle problem by finite difference method. We prove the existence and uniqueness of the solution of the discrete nonlinear system and obtain an error estimate for the corresponding regularization. Also we prove the convergence of the proposed numerical algorithm. At the end of the paper we present some numerical simulations.